PENINGKATAN PENGUASAAN GRAMATIKA DALAM MENULIS BAHASA5 INGGRIS MELALUI TEKNIK PROBLEM SOLVING Penelitian Tindakan di - Rahman Apen (Program Studi Pendidikan Bahasa Program Pascasarjana Universitas Negeri Jakarta, 2016)
This article is aimed at describing the process and the result in improving grammar mastery in writing English of English Education Study Program in State University ofPadang through problem solving technique. The subject of the research was 30 students who took Grammar I subject in even semester of academic year 201112012. The instruments used are: questionnaire.students' portfolio, observers' journals, researcher's journal, pre-test, and post-test. The data were analyzed by using the descriptive statistic in the form of the mean and percentage, and the validity of the data was Checkedby using triangulation technique. The results of the study show that 1) the process in improving grammar mastery in writing English through problem solving technique ran well. 2) Theresultof improvementon the grammar mastery in writing English varied within the three cycles of different instructional activities conducted. The indicators were seen from the pre-to post test results. of each cycle. The results in writing English sentence mastery through classical instructional activities improved from 2,4 (limited to moderate) to 3,6 (moderate to extensive). In group discussion activities the improvement is from 3,36 (moderate to extensive) 3,7 (moderate to extensive). Meanwhile, the improvement is seen from 3,8 (moderate to extensive) to 4,6 (extensive to complete) in pair work instructional activities. Based on the results, the learning processthrough problem solving technique can improve the learning results of grammar mastery in writing English. In other words, the hypothesis of action proposed is accepted.